Objective assessment of the factors affecting outcome of immediate management of mandibular fractures – A prospective study in a Level-I trauma care center - Tushar Dutta; Sandip Basu (Asian Journal of Medical Sciences, 2023)
Background: Mandibular fractures lead to complications if improperly treated. The management of mandibular fractures includes open reduction and internal fixation (ORIF) or closed reduction. Associated complications include malocclusion, infection, hardware extrusion, and nerve injury.